Developing Community-Based Solid Waste Management (CBSWM) Model: Case of West Nusa Tenggara, Indonesia - Ramadhanti, Fati (Budapest International Research and Critics University, 2022)
The second largest food waste and plastic waste producer in the sea, Indonesia is faced with serious challenges when it comes to waste management. Nusa Tenggara Barat (NTB) is a province in Indonesia that urgently prioritizes waste management. Community-Based Solid Waste Management (CBSWM), a solid waste management system with many proven benefits, is popularly used in many developing countries including Indonesia. Aimed at developing the CBSWM model in NTB, this study was conducted by collecting the primary data through the FGD process as well as the secondary data. This study found that although the local communities had the motivation and willingness to manage their solid waste, they had limited knowledge and skills. The CBSWM model is expected to accelerate the solid waste management activities in NTB.